(untitled) (International Journal of Engineering and Computer Science, 2017)
With the increase in amout of data and information one has to deal with,now a days,going through all the documents is a time consuming process.We are implementing an android application that helps organizations such as law firms to manage the hundreds of documents and to get summary of these documents.We are also using concept of ontology for this application.Ontology is basically the relationship between entities.The application that we are implementing allow the users to search for files in the database,upload files and summarize multiple documents.